Research Mapping of E-Module Integration with Problem Based Learning Model in Physics Learning: A Bibliometric Analysis - Wiska, Wiska Cahyandari; Feziyasti, Azifa; Asrizal, Asrizal (Journal of Innovative Physics Teaching, 2025)
Twenty first century education emphasizes the development of critical thinking, creativity, collaboration, communication, and problem-solving skills through the use of digital technology and innovative learning models. This study aims to map and analyze the effectiveness of integrating the Problem-Based Learning (PBL) model into e-modules to improve students' problem-solving skills in physics learning. This study employed bibliometric analysis by reviewing literature published between 2017 and 2025, using VOSviewer software for data visualization and analysis. The documents analyzed were articles indexed in the Scopus database, selected based on their relevance to the development, implementation, or integration of e-modules in physics education that use or are related to the Problem-Based Learning (PBL) model. These findings reveal that research on PBL integration in e-module development is still relatively new, but shows promising potential for innovation in physics learning. Network and density visualizations indicate that this topic is continuously evolving and aligned with current educational demands. Recent trends indicate that integrating PBL into e-modules can significantly improve students' problem-solving skills while addressing low academic achievement. Therefore, this study highlights the importance of implementing innovative learning models as a strategic effort to improve the quality of learning and educational outcomes in the 21st century.